Sistem Pendukung Keputusan Penentuan Mutu Tanaman Karet (Studi Kasus PT. Hevea MK 1) - Yulianti, Evi; Marcelina, Dona; Aulia, Muti’a Rahma (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
Determination of Product Quality of Hevea Brasiliensis (Rubber) at PT. Hevea MK 1 Palembang is very important in improving the quality of service to consumers. PT. Hevea MK 1 Palembang has not maximally utilized Information System Technology in determining the best quality of latex, resulting in a relatively long time in calculating the quality value of latex rubber, the need for Information Systems Technology that can support Decision Making to solve structured and unstructured problems. Based on the problems above, we need a system that can solve the quality problem of Hevea brasiliensis (rubber) sap, with the Decision Support System determining the quality of Hevea Brasiliensis (rubber) sap is expected to help and facilitate the company in choosing the type of superior rubber seeds. This study aims to determine the best quality of latex Hevea Brasiliensis rubber at PT. Hevea MK 1 Palembang uses the promethee method. The output of this application is in the form of an alternative decision with the highestranking value. The Decision Support System was developed using PHP and MySQL programming as a Database Management System (DBMS). System testing resulted in Rank 1, namely A2 with Leaving Flow = 0.583333, Entering Flow = 0, Net Flow = 0.583333 while Rank 2, namely A3 with Leaving Flow = 0.166667, Entering Flow = -0.25, Net Flow = -0 .8333 and Rank 3, namely A1 with Leaving Flow = 0, Entering Flow = 0.5, Net Flow = -0.5